Momento adutor do joelho durante a marcha, torque abdutor do quadril e biomarcadores : estudo na progressão da Osteoartrite de joelho - Selistre, Luiz Fernando Approbato (2017)
Introduction: Hip abductor strength has been targeted in rehabilitation programs for patients with knee osteoarthritis, however, as it explains only a small portion of medial knee load, the influence of trunk, pelvis, and hip kinematics in the frontal plane during gait in this population should be investigated. This study aimed to investigate the relationship of hip abductors strength with hip and knee adduction moments, pain and physical function, and trunk, pelvis, and hip kinematics during walking in the frontal plane in subjects with medial knee osteoarthritis. Methods: Twenty five subjects with medial knee osteoarthritis were included in the study. Participants were evaluated through an isokinetic strength test for hip abductors, three-dimensional gait analysis, the WOMAC pain and physical function scores, and walk test – 40m. First, the relationship of hip abductor strength with the other variables was investigated. Second, regression models were used to control the influence of other parameters such as pain, age, gender, severity, walking speed, mass and height. Results: Hip abductors strength explained 17% of contralateral pelvic drop and 21% of hip adduction angle. In addition, hip abductors strength explained 4% and 1% of the variance in the WOMAC physical function score and walk test (40m), respectively. Conclusion: Considering the relationship of hip abductors strength with contralateral pelvic drop and hip adduction angle, specific exercises should be used to improve physical function and the ability of hip abductors to stabilize the pelvis and the hip adduction angle during walking.